KAJIAN KOMUNIKASI ISLAM YASINAN DAN TABLILAN DALAM PANDANGAN MASYARAKAT - Muhtadin, Muhtadin (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2010)
Communication in Islam is a religious proselytizing (da 'wa) to invite people to believe and practice Islamic faith (aqidah) and law (Shari, a). Yasinan means reciting the verse of Yasin together either in Friday night or certain nights in mosques, praying rooms, or in any hoeses that need it. Tahlil means reciting the verse of "laa ilaaha illallaah ", Tahlilan means collectively pray for other people such as family. relatives or frends, etc. Who have died in order to gain the acceptance of their deeds and to receive Allah s forgivenessfor their faults and sins. Inwriters perspective, the Yasinan and Tahlilan are still debatable in society. Therefore the writer aims at analyz ing the argumentations (dalil) or foundations used by those who are pro and con. In tum, society hopefally could understand them. Additionally, this study hopefully could give benefit for Islamic Umma in general and the writer as well.